Representing the Ideal: The Portrait of the Sanguine in Cesare Ripa’s Iconologia - Koźluk, Magdalena (Studia Ceranea, 2025)
This article is the fourth and final in a series of works aimed at contributing to the documentation of the success of the medical theory of individual complexions, derived from the theory of the four humours, through the major work of the Italian humanist Cesare Ripa (1555–1622), the Iconologia. We study the allegory of the sanguine complexion, whose primacy over the other three is explicitly established in medical tradition. We analyze, through the allegorical attributes mentioned in the text (youth, joy, a crown of flowers, a ruddy face tinged with white, a lute, an open book of music, a ram grazing on a cluster of grapes), the way in which Ripa seeks to portray this ideal of health. We also demonstrate that the author slightly diverges from the medical canon. Firstly, his extensive synthesis of the doctrine leads him to introduce certain pathological dissonances, perceptible in the use of unexpected terms. Secondly, to account for a well-tempered character, he prefers to follow an ancient literary tradition which, nonetheless, maintains very close links with the Hippocratic corpus since its origins. Finally, it appears that the Sanguigno per l’aria contains no new symbolic invention, matching what we previously observed in the Flemmatico and the Malenconico.